The Role of Accounting Information Systems in Disclosure of Environmental Costs: A Case Study of Zawiya Oil Refining Company for the Year 2017 - Ahmad, Khaled Albashir Muhammad; Al-Mazoughi, Omar Misbah (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to identify the role of accounting information systems in disclosing environmental costs by calculating and disclosing the costs of environmental pollutants in the port and marine facilities resulting from the company's operational process. The study aimed to demonstrate the role of accounting information systems in disclosing environmental costs within the company using qualitative and quantitative approaches, and using content analysis to analyze the final financial statements. The study concluded that accounting information systems do not play a role in disclosing environmental-related costs within the company and are absent as environmental information in the final financial statements. The study recommended the necessity of disclosing environmental costs by relying on the proposed disclosure model to demonstrate the role of information systems in disclosing environmental costs.
Keywords: Accounting Information Systems; Accounting Disclosure; Environmental Costs